Application of Multivariate Statistical Delineation of Prospective Geochemical Providenskaya Area (Chukotka, Russia); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Kirillova M.; Voroshilov V. G. Valery Gavrilovich; Yankovich A.; Yankovich E. P. Elena Petrovna; Maskov A.; Chernyshov A. (Ore Deposits: Current Prospecting and Exploration Methods, 2016)
Title screen